The efficacy of the thyroid peroxidase marker for distinguishing follicular thyroid carcinoma from follicular adenoma - Savin, S.; Cvejic, D.; Isic, T.; Paunovic, I.; Tatic, S.; Havelka, M. (Experimental Oncology, 2006)
Aim: Expression of thyroid peroxidase (TPO) in the thyroid gland tissue is well known as a sensitive marker of the thyroid malignancy. We have evaluated immunohistochemical assay of TPO for distinguishing follicular thyroid carcinoma from follicular adenoma. Materials and Methods: Sections of formalin-fixed tissues obtained from 92 patients with thyroid tumors (52 follicular carcinomas and 40 follicular adenomas including the Hurthle cell type) were analyzed using a monoclonal antibody (TPO mAb 47) and the avidin-biotin peroxidase complex immunohistochemical technique. Lesions with staining of more than 80% of the follicular cells/specimen were considered benign, while less than 80% were considered malignant. Results: TPO immunostaining correlated with the histopathological diagnosis in 24/40 cases of follicular adenomas and 41/52 cases of follicular carcinomas, giving a specificity of 60% and a sensitivity of 79%. Conclusion: These results suggest that immunohistochemical assay of TPO expression has limited value for the differential diagnosis of follicular thyroid carcinoma from thyroid follicular adenoma. Цель: уровень экспрессии тироидной пероксидазы (ТПО) в ткани щитовидной железы является чувствительным маркером малигнизации этого органа. В работе представлено попытку оценки метода иммуногистохимический детекции
ТПО для дифференциальной диагностики фолликулярной карциномы и фолликулярной аденомы щитовидной железы
(ФКЩЖ и ФАЩЖ соответственно). Материалы и методы: срезы ткани, зафиксированные в формалине, были получены
у 92 пациентов с опухолями щитовидной железы (52 случая — ФКЩЖ и 40 — ФАЩЖ, в том числе тип с клетками Хюртля). Для иммуногистохимического анализа этих срезов использовали моноклональные антитела против ТПО (ТРОmAb47)
и авидин-биотиновый комплекс. Препараты опухолей, содержащих более 80% позитивно окрашенных фолликулярных
клеток, признавали доброкачественными, а те, что содержали менее 80% таких клеток, — злокачественными. Результаты: интенсивность иммуноокрашивания препаратов коррелировала с гистопатологическим диагнозом в 24 из 40 случаев
ФАЩЖ и в 41 из 52 случаев ФКЩЖ. При этом чувствительность метода составляла 79%, специфичность — 60%.
Выводы: иммуногистохимический анализ ТПО имеет недостаточную специфичность для дифференциальной диагностики
фолликулярной карциномы и фолликулярной аденомы.